PERLINDUNGAN HAK EKONOMI PENCIPTA ATAS KARYA FONT DI PLATFORM DIGITAL - Asrofi, Muchtar Hasan (JIPRO: Journal of Intellectual Property, 2025)
The installation process of Fonts differs from the installation process of software such as operating system and application programs. Software installation requires a verification phase based on codes, whereas Fonts do not. This is why software usage can be tracked, while Font usage cannot. As a result, Font creators are unable to monitor/ track whether their Fonts are being used in accordance with the license terms or not. This situation creates a potential loss for Font creators because the economic rights granted to licensees become unlimited. The aim of this research is to gain a conceptual or a philosophical understanding of the protection of the creator’s economic rights over Font on digital platforms based on the Incentive Theory. This is a normative legal study using a conceptual and statutory approach. The results of this research indicate that Font are protected creations which classified as compilations of data that can be read by computer programs, and thus their creators have the economic rights over them. Incentive Theory provides the fundamental principle or concept for protecting the economic rights of Font creators in Indonesia, in order to appreciate their creative efforts, encourage the emergence of other economically valuable works, and ensure a decent livelihood. The protection of the economic rights needs to be facilitated by the Government. Keywords : Font, Compilations of Data, Economic Right, Protection Abstrak. Proses instalasi Font berbeda dengan software sistem operasi maupun program aplikasi. Proses instalasi software membutuhkan tahap verifikasi berbasis kode, sedangkan Font tidak. Hal itu yang menyebabkan software dapat dilacak penggunaannya, sedangkan Font tidak bisa. Dampaknya, kreator Font tidak bisa melacak penggunaan Font apakah sesuai dengan ketentuan dalam lisensi atau sebaliknya. Keadaan seperti itu menimbulkan potensi kerugian bagi kreator Font karena pemakaian hak ekonomi oleh penerima lisensi menjadi tidak terbatas. Tujuan dari penelitian ini yakni mendapat pemahaman konseptual terhadap perlindungan hak ekonomi Pencipta atas karya Font di platform digitalberdasarkan Teori Insentif. Penelitian ini merupakan penelitian normatif dengan pendekatan konseptual dan perundang-undangan. Hasil dari penelitian ini adalah Font merupakan ciptaan yang dilindungi yang mana digolongkan sebagai kompilasi data yang dapat dibaca program komputer sehingga penciptanya mempunyai hak ekonomi atas ciptaan tersebut. Teori insentif memberikan prinsip/ konsep dasar perlindungan hak ekonomi kreator Font di Indonesia guna menghargai upaya kreatifnya, mendorong lahirnya karya bernilai ekonomi lain, dan menciptakan penghidupan yang layak. Perlindungan hak ekonomi perlu difasilitasi oleh Pemerintah. Kata Kunci : Font, Kompilasi Data, Hak Ekonomi, Perlindungan